Universal child policies, child development and parental behavior - Jonas Lau-Jensen Hirani (University of Copenhagen, Department of Economics, 2020)
This dissertation consists of four self-contained chapters. Each chapter can be read independently but jointly they contribute to the understanding of the interactions between parental behavior and public policies in shaping child development. I use natural experiments, quantitative methods and various data sources to investigate the causal links between aspects of universal programs and family well-being and behavior. Chapter 1 studies one of the first universal child policies in Denmark, namely a family planning program introduced in 1939 as a political response to decades of declining fertility and widespread use of illegal abortions to terminate pregnancies. The family planning program served as an instrument to reverse both these tendencies. Chapter 2 investigates the contemporary nurse home visiting program for infants in Denmark. Using a national nurse strike in 2008, the chapter studies how the timing of nurse visits impacts child and maternal health. Chapter 3 studies why some parents fail to adhere to the recommendations of the Danish Childhood Vaccination Program by exploiting parental responses to vaccination reminder letters. Chapter 4 explores the interaction between the nurse home visiting program and other preventive care programs for infants in Denmark. Specifically, the chapter studies if nurses during home visits encourage parental health investments measured as adherence to the recommendations in the vaccination and GP health check programs.
Keywords: 330